2020
DOI: 10.1021/acs.jced.0c00407
|View full text |Cite
|
Sign up to set email alerts
|

Volumes and Heat Capacities of Cobalt(II), Nickel(II), and Copper(II) Sulfates in Aqueous Solution

Abstract: Densities and isobaric volumetric heat capacities of aqueous solutions of the sulfate salts of cobalt(II), nickel(II) and copper(II) have been measured at 298.15 K and 0.1 MPa using vibrating tube densimetry and Picker flow calorimetry, respectively, at concentrations in the range 0.01 ≲ m/mol•kg -1 ≲ 1.5. These data were used to derive the corresponding apparent molar volumes, V, and apparent molar isobaric heat capacities, Cp.Where comparisons were possible the present V results were in good agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The temperature dependence of V o (Tf – , aq) over the range 293.15 ≤ T /K ≤ 343.15 K was well described by The values of V o (Tf – ) as a function of temperature will be particularly useful for characterizing the standard volumes, V o (M z + ), of higher charged ( z > 1) metal cations because of the minimal tendency of Tf – to associate (ion pair) with such cations. ,, This feature is important because most of the higher valent salts that have been used to date for such purposes contained anions (such as the halide ions or sulfate) that are known to bind metal ions, at least to some extent. , As is well understood, even relatively minor levels of self-association can have significant effects on the observed V ϕ ( m ) values and can introduce serious uncertainties into their extrapolation to infinite dilution …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence of V o (Tf – , aq) over the range 293.15 ≤ T /K ≤ 343.15 K was well described by The values of V o (Tf – ) as a function of temperature will be particularly useful for characterizing the standard volumes, V o (M z + ), of higher charged ( z > 1) metal cations because of the minimal tendency of Tf – to associate (ion pair) with such cations. ,, This feature is important because most of the higher valent salts that have been used to date for such purposes contained anions (such as the halide ions or sulfate) that are known to bind metal ions, at least to some extent. , As is well understood, even relatively minor levels of self-association can have significant effects on the observed V ϕ ( m ) values and can introduce serious uncertainties into their extrapolation to infinite dilution …”
Section: Resultsmentioning
confidence: 99%
“…3,6,10 This feature is important because most of the higher valent salts that have been used to date for such purposes contained anions (such as the halide ions or sulfate) that are known to bind metal ions, at least to some extent. 29,30 As is well understood, even relatively minor levels of selfassociation can have significant effects on the observed V ϕ (m) values and can introduce serious uncertainties into their extrapolation to infinite dilution. 29 ■ CONCLUSIONS Apparent molar volumes, V ϕ , for sodium and potassium triflates in aqueous solutions, derived from density measurements, vary smoothly over the temperature range 293.15 ≤ T/ K ≤ 343.15 up to very high concentrations (of ∼7 and ∼16 mol•kg −1 , respectively).…”
Section: Standard Partial Molarmentioning
confidence: 99%
“…Whilst DH theory is often considered capable of only accounting for phenomena in dilute aqueous environments (o10 À3 M), for long-range electrostatic interactions it is often adequate up to concentrations of B0.5 M. 114 The extended DH model of Stokes and Robinson, 115 which includes a description of the ionic radius, is accurate up to B0.1 M. Similarly, specific ion interaction theory was developed from DH theory to estimate single ion activity coefficients at even higher concentrations (B10 M) via interaction coefficients. 116,117 The Pitzer Method 118 has become an increasingly popular tool for determining the thermodynamic properties of electrolytes [119][120][121][122] and is considered the best model for predicting ion activity coefficients to date. 123,124 Nevertheless, it too is based on DH theory, although it also accounts for the hydrated size of individual ions and their short-range binary and ternary interactions via a virial expansion (thereby requiring additional empirical parameterisation).…”
Section: Ion Solvation In Watermentioning
confidence: 99%
“…Brodale and Giauque [14] and Goldberg et al [17] have reported some heats of solution measurements for cobalt sulfate heptahydrate and hexahydrate at low concentrations and near ambient conditions. Solution heat capacities have been reported only by Akilan et al [18].…”
Section: Selected Datamentioning
confidence: 99%
“…As such, experimental activity data is needed, which, unfortunately for these systems, does not appear to be available. It has been noted previously that the thermodynamic properties of the bivalent sulfates show striking similarities, as evidenced by their ion-pairing stability constants [36], osmotic coefficients [59], heat capacities and volumetric properties [18] and dielectric relaxation behaviour [37,38], to…”
Section: Further Developmentsmentioning
confidence: 99%